Emotional Comparison Between Semantic Dementia and Alzheimer's Disease - Wang, Ping; Zhao, Qianhua; Zhou, Yan; Hong, Zhen; Guo, Qihao; Liu, Jianren (Frontiers in Psychiatry, 2021)
Background: Previous studies have suggested that Alzheimer’s disease (AD) and semantic dementia (SD) are both associated with emotional processing impairment. However, the degree and type of emotional symptoms between the two types of dementia have not been previously compared. Method: We used the Apathy Evaluation Scale (AES), the Toronto Empathy Questionnaire (TEQ), the Geriatric Depression Scale (GDS) and the Self-rating Anxiety Scale (SAS) to examine apathy, empathy, depression and anxiety respectively. Results: Between mild AD and mild SD, moderate-to-severe AD and moderate-to-severe SD, the total scores of TEQ are significantly different, but the total scores of GDS, SAS and AES have no significant differences. In addition, normal individuals, AD and SD patients got the similar scores in SAS and GDS. Conclusions: Empathy emotion in SD patients is more severe than that in AD patients. However, apathy, depression and anxiety emotion is similar between the two groups.